2020
DOI: 10.1111/joa.13176
|View full text |Cite
|
Sign up to set email alerts
|

Appendicular myological reconstruction of the forelimb of the giant titanosaurian sauropod dinosaur Dreadnoughtus schrani

Abstract: Soft tissues are variably preserved in the fossil record with external tissues, such as skin and feathers, more frequently preserved than internal tissues (e.g. muscles). More commonly, soft tissues leave traces of their locations on bones and, for muscles, these clues can be used to reconstruct the musculature of extinct vertebrates, thereby enhancing our understanding of how these organisms moved and the evolution of their locomotor patterns. Herein we reconstruct the forelimb and shoulder girdle musculature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(94 citation statements)
references
References 53 publications
2
92
0
Order By: Relevance
“…Alternatively, Wilhite (2005) and Silva Junior et al (2019) suggested that this area could instead correspond to a ligamentous connection between the tibia and fibula. It is possible that this area could represent attachment of both muscle and ligament, as has been previously suggested for soft tissues connecting the radius and ulna via the interosseous ridge of the former bone (Voegele et al, 2020, and references therein).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Alternatively, Wilhite (2005) and Silva Junior et al (2019) suggested that this area could instead correspond to a ligamentous connection between the tibia and fibula. It is possible that this area could represent attachment of both muscle and ligament, as has been previously suggested for soft tissues connecting the radius and ulna via the interosseous ridge of the former bone (Voegele et al, 2020, and references therein).…”
Section: Resultsmentioning
confidence: 76%
“…Scarcity of myological investigations of sauropods, in general, including well‐preserved and fairly complete titanosaurian taxa (e.g., Rapetosaurus , Curry Rogers, 2009; Saltasaurus , Powell, 2003), combined with a general lack of quantity and quality of preservation for the clade as a whole, has greatly limited our understanding of titanosaurian appendicular musculature. Only a few previous species‐level myological studies have been completed for members of Titanosauria (Borsuk‐Bialynicka, 1977; Ibiricu et al, 2018; Klinkhamer et al, 2018, 2019; Otero & Vizcaíno, 2008; Voegele et al, 2020). Alternatively, descriptions of sauropod appendicular material occasionally include discussion of probable osteological correlates for muscle attachment (e.g., Curry Rogers, 2009; Gallina & Apesteguía, 2015; Harris, 2007; Silva Junior et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Extant crocodylians are naturally used for morphological comparison when it comes to fossil crocodyliforms ( Langston, 1995 ; Denton, Dobie & Parris, 1997 ; Hua, 2003 ; Jouve, Bouya & Amaghzaz, 2005 ; Jouve et al, 2006 ; Schwarz, Frey & Martin, 2006 ; Schwarz-Wings, Frey & Martin, 2009 ; Hastings et al, 2010 ; Hastings, Bloch & Jaramillo, 2011 , 2014 ; Schwarz-Wings, 2014 ; Martin, Sarr & Hautier, 2019 ) or other archosaurs ( Maidment & Barrett, 2011 ; Liparini & Schultz, 2013 ; Voegele et al, 2020 ), and also serve as behavioral and functional archetypes (e.g. Hua & Buffetaut (1997) ; Jouve et al (2008) ; Schwarz-Wings, Frey & Martin (2009) ; Schwarz-Wings (2014) ).…”
Section: Introductionmentioning
confidence: 99%
“…Luckily, direct evidence of muscles is often preserved by the surface texture of bones. Osteological correlates of muscles are created as a muscle exerts stress on the underlying bone (Bryant & Seymour, 1990;Frankel & Nordin, 2001;Voegele et al, 2020;Voegele et al, 2021). Such textures indicate where muscles would have attached to the bone, the minimum size of the attachment area, and even the type of attachment.…”
Section: Methodsmentioning
confidence: 99%
“…Such textures indicate where muscles would have attached to the bone, the minimum size of the attachment area, and even the type of attachment. Unfortunately, not all muscles will produce visible texturing, nor will the entire attachment area be preserved (Bryant & Seymour, 1990;Dilkes et al, 2000;Dilkes et al, 2012;Voegele et al, 2020;. As such, when reconstructing the myology of fossil organisms, it is often necessary to rely on comparisons with the extant phylogenetic bracket (EPB).…”
Section: Methodsmentioning
confidence: 99%